STUDI KUALITAS PELAYANAN LISTRIK TERHADAP KEPUASAN PELANGGAN PT PLN (PERSERO) RAYON TABANAN - Supardiasa, I Putu; Maharta Pemayun, AA Gede; Rinas, I Wayan (Jurnal SPEKTRUM; Vol 4 No 2 (2017): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2017.v04.i02.p20, 2018)
The level of satisfaction with the service provided by PLN becomes the main priority that must be obtained by the customers. The purpose of this research is to know the quality of electricity service to customer satisfaction PT PLN (Persero) Rayon Tabanan. In this research using 100 respondents by using non random sampling method in sample selection. There are two methods used in the research is the method of statistical data and methods of observation. Statistical data is the result of respondents' assessment on importance performance analysis, validity test and Cartesian diagram. Observation is a direct observation in the study. The results of this study indicate that electricity customers Rayon Tabanan feel satisfied with the quality of electricity service PT PLN (Persero) Rayon Tabanan because the assessment of respondents on electrical continuity in the level that is felt in accordance with the expected customers with SPSS calculation of 4.59% and for the value the lowest of 3.49% is the speed of PB / PD / PS application.